A dynamic estimation of governance structures and financial performance for Singaporean companies - Nguyễn, Văn Tuấn (2022)
In this study, a sample of 257 Singaporean domiciled non-financial listed companies is investigated using a system generalised method of moments (system GMM) estimator. This approach allows for controlling the potential sources of endogeneity which are inherent in the performance–governance relationship. Our findings strongly support the proposition that the relationship between corporate governance structures and firm performance is dynamic by nature. Moreover, our results show that the internal corporate governance structures do matter in Singapore, where the market for corporate control is relatively poor. This study is novel as it is the first to explore the corporate governance–firm performance nexus using a dynamic approach for the Singapore market. This study significantly contributes to a better understanding of international diversity on corporate governance by providing further empirical evidence from an emerging market characterised by the best corporate governance practices in the Asian region.